A diffusion tensor imaging study in HIV patients with and without apathy - Fouche, Jean-Paul (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScMedSc (Biomedical Sciences. Medical Physiology))--University of Stellenbosch, 2010.